Fecal calprotectin levels are higher in rural than in urban Chinese infants and negatively associated with growth - Liu Jin-Rong; Sheng Xiao-Yang; Hu Yan-Qi; Yu Xiao-Gang; Westcott Jamie E; Miller Leland V; Krebs Nancy F; Hambidge K (BMC, 2012)
Abstract Background Fecal calprotectin (FC) is an established simple biomarker of gut inflammation. To examine a possible relationship between linear growth and gut inflammation, we compared fecal calprotectin levels in 6 month old infants from poor rural vs affluent urban families. Methods The project was a cross-sectional comparison of FC from rural and urban populations in China. The relationship between length-for-age Z-score (LAZ) and FC concentrations were also compared. Single fecal samples were assayed for FC using EK-CAL ELISA kits. Results The age of subjects for both locations was 6.1 ± 0.2 mo; all were apparently healthy. The mean ± SD of the LAZ for the rural and urban infants were −0.6 ± 0.9 and 0.4 ± 0.9, respectively. FC had a non-normal distribution. The median FC of 420.9 and 140.1 μg/g for rural and urban infants, respectively, were significantly different (P < 0.0001). For the rural group, linear regression analysis showed that an increase in FC of 100 μg/g was associated with a decrease of 0.06 in LAZ. Conclusion FC levels were significantly elevated in the rural infants and high concentrations accounted for approximately one-third of the low LAZ scores of these infants.